A Pilot Survey of an M Dwarf Flare Star with Swift's UV Grism - Chavali, Shashank; Youngblood, Allison; Paudel, Rishi R.; Loyd, R. O. Parke; Molaverdikhani, Karan; Pineda, J. Sebastian; Barclay, Thomas; Vega, Laura D. (AAS, 2022)
The near-ultraviolet (NUV) spectral region is a useful diagnostic for stellar flare physics and assessing the energy environment of young exoplanets, especially as relates to prebiotic chemistry. We conducted a pilot NUV spectroscopic flare survey of the young M dwarf AU Mic with the Neil Gehrels Swift Observatory's UltraViolet and Optical Telescope. We detected four flares and three other epochs of significantly elevated count rates during the 9.6 hr of total exposure time, consistent with a NUV flare rate of ∼0.5 hr−1. The largest flare we observed released a minimum energy of 6 × 1033 erg between 1730 and 5000 Å. All flares had durations longer than the ∼14–17 minutes duration of each Swift visit, making measuring total flare energy and duration infeasible.